Filosofis dan Makna Bale Sakanem di Petang, Badung. - Desak Made Sukma Widiyani,S.T.,M.T; Suratmi, Ni Luh (Universitas Dwijendra, 2020)
Traditional Balinese house architecture is a work that is born from the traditions, beliefs and spiritual activities of the Balinese people which are manifested in various physical forms, such as traditional houses, sacred places (places of worship called temples), meeting halls, and others. The birth of various physical manifestations is also caused by several factors, namely the geography, culture, customs, and socio-economic conditions of the community. One of the buildings in a traditional Balinese house is the Bale Dangin. Bale Dangin is located in the eastern part of the Balinese Hindu community yard. Bale Dangin has the main function as a place to make and place ceremonies for Manusa Yadnya ceremonies such as metatah (tooth cutting), otonan, pewiwahan natab in bale and other activities. Along with the development of the times like nowadays, Bale Dangin buildings are rarely found in Hindu community houses in Bali, there are several factors affecting this, from the land that is owned is narrow / only enough for the main building to the factor that people are less interested in traditional buildings on the grounds that they are not modern and with the times. So that there is a change in the meaning of the Bale Dangin Building itself. In addition to changes in meaning, there is also a change in the materials used in the construction of the Bale Dangin building, after searching data by interviewing and field observations, it is known that things that affect changes in the use of Bale Dangin materials are due to climate / weather, developments existing architectural styles and the state of the community economy. The purpose of this research is to discuss how the function and meaning of the existence of Bale Dangin, especially Bale Dangin Sakanem in Hindu community homes in Bali, and to find out what materials can be used to produce Bale Dangin buildings that are still up to date with the times but do not reduce the value of philosophy and meaning of Bale Dangin itself so that it can survive amid the development of architectural styles in Bali.